Pemberdayaan Masyarakat dalam Pengembangan Wisata Bahari Taman Laut Olele di Kabupaten Bone Bolango - Setiawan, Dewa Gede Eka; Lipoeto, Moh. Ramdan; Kurniasari, Septiana (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Olele Marine Park is a marine tourism destination that has great potential because of its underwater beauty and biological wealth. However, this potential has not been fully utilized by the surrounding community to its full potential. This community service activity aims to increase community involvement in managing tourism areas through environmental education, tourism awareness training, and strengthening local institutions. The methods used are field observation, group discussions, and direct assistance to the community. The results of the activity show an increase in community understanding of the importance of maintaining the cleanliness of the tourism environment, preserving coral reefs, and basic skills in tourism services. Tourism development that directly involves the community has proven to be able to build a sense of ownership and encourage the growth of local initiatives in managing tourism areas sustainably.